2014
DOI: 10.1186/1758-5996-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Excess body mass index loss predicts metabolic syndrome remission after gastric bypass

Abstract: BackgroundMetabolic syndrome (MS) is a condition associated with obesity that identifies individuals with increased cardiovascular risk. Gastric bypass improves several MS components, such as glucose, lipid metabolism and hypertension. The aim of this study was to evaluate the effect of long-limb gastric bypass on the remission of MS criteria associated with morbid obesity.MethodsObese patients who met the “harmonized” criteria for MS (n = 153) that underwent laparoscopic Roux-en-Y gastric bypass (LRYGB) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 46 publications
1
39
0
1
Order By: Relevance
“…Diabetes, on the other hand, tends to be underreported which suggests that our results provide a lower bound of the diabetes burden in Brazil. For instance, data from the Brazilian Longitudinal Study of Adult Health, a cohort study of adult civil servants aged 35–74 years found that 50.4 % of the individuals with diabetes were undiagnosed [15]. In addition, accuracy of self-reports may also vary depending on socioeconomic characteristics, such as educational level and access to health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes, on the other hand, tends to be underreported which suggests that our results provide a lower bound of the diabetes burden in Brazil. For instance, data from the Brazilian Longitudinal Study of Adult Health, a cohort study of adult civil servants aged 35–74 years found that 50.4 % of the individuals with diabetes were undiagnosed [15]. In addition, accuracy of self-reports may also vary depending on socioeconomic characteristics, such as educational level and access to health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly in Brazil, as in most countries, socioeconomic differences in health are largely driven by differences in educational attainment [10] whereby those with low levels of education tend to be in vulnerable positions leading to worse health outcomes relative to those with high education (this is commonly referred to as educational gradients in health). For instance, most studies in Brazil have found higher prevalence of diabetes among adults with lower education than among those with higher educational levels [1115]. Goldenberg and colleagues found that whereas women that are more educated had lower prevalence of diabetes, the reverse was found among men in Sao Paulo [16].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, hypertension is the leading cause of cardiovascular diseases (CVD) and deaths [ 1 ], and accounts for about 7.5 million deaths per year [ 2 ]. Hypertension tends to occur in clusters with other cardiovascular diseases such as type 2 diabetes (T2DM) and dyslipidaemia.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the United States, the prevalence of this syndrome in the 40-59 year age group is 40% and 34% in men and women, respectively. 15 Osteoarthritis secondary to morbid obesity is also a well-described and expected finding.…”
Section: Discussionmentioning
confidence: 92%